2008
DOI: 10.1007/s00572-008-0215-0
|View full text |Cite
|
Sign up to set email alerts
|

The arbuscular mycorrhizal symbiosis links N mineralization to plant demand

Abstract: Arbuscular mycorrhizal (AM) fungi facilitate inorganic N (NH(4)(+) or NO(3)(-)) uptake by plants, but their role in N mobilization from organic sources is unclear. We hypothesized that arbuscular mycorrhizae enhance the ability of a plant to use organic residues (ORs) as a source of N. This was tested under controlled glasshouse conditions by burying a patch of OR in soil separated by 20-microm nylon mesh so that only fungal hyphae can pass through it. The fate of the N contained in the OR patch, as influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
5
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(66 citation statements)
references
References 48 publications
2
55
5
4
Order By: Relevance
“…When the fungus had access to organic patches that were labelled with 15 N and 13 C, the fungal ERM got only enriched with 15 N, but not with 13 C. This confirms that AM fungi do not have saprophytic capabilities and that the fungus acquires 15 N from these organic patches likely as a decomposition product [105]. However, even if AM fungi themselves do not act as decomposers, AM fungi accelerate the N mineralization from organic matter [107] and affect the carbon flow through soil microbial communities during decomposition [108].…”
Section: Uptake Of Organic N By Hyphaementioning
confidence: 57%
“…When the fungus had access to organic patches that were labelled with 15 N and 13 C, the fungal ERM got only enriched with 15 N, but not with 13 C. This confirms that AM fungi do not have saprophytic capabilities and that the fungus acquires 15 N from these organic patches likely as a decomposition product [105]. However, even if AM fungi themselves do not act as decomposers, AM fungi accelerate the N mineralization from organic matter [107] and affect the carbon flow through soil microbial communities during decomposition [108].…”
Section: Uptake Of Organic N By Hyphaementioning
confidence: 57%
“…Brassica crops are not mycorrhizal compatible (Brundrett 2009) and their roots usually lack any functional mycorrhizal activity (Glenn et al 1984). It is unknown whether or not the low N mineralization under oilseeds was reflected to a lack of arbuscular mycorrhizal symbiosis, but Nayyar et al (2009) found positive influences of mycorrhizal activity on soil N mineralization in canola. Maize plants inoculated with vesicular-arbuscular mycorrhizal (VAM) fungi increased root dry matter yield and the amount of N mineralized significantly compared to maize plants without VAM inoculation (Paré et al 2000).…”
Section: Nitrogen Mineralizationmentioning
confidence: 92%
“…Available evidence for AM fungal involvement AM fungi assimilate N either exclusively (Tanaka and Yano, 2006) or predominantly (Govindarajulu et al, 2005) in the form of NH þ 4 . Moreover, evidence accumulates that AM fungi may possess the ability to mobilize N from organic sources (Hodge et al, 2001Atul-Nayyar et al, 2009;Leigh et al, 2009;Barrett et al, 2011). Abovementioned studies have revealed that the N mobilized from patches can account for up to 32% of the total N present in the patch (Leigh et al, 2009), that N mobilization is possible at temperatures close to 10 C (Barrett et al, 2011) and that N mobilization may take place even when an AM fungus fails to stimulate plant growth .…”
Section: Am-mediated Effects On Individual N-cycling Processesmentioning
confidence: 99%